Membumikan Pesan Al-Qur'an: Analisis Terjemah Ayat-Ayat Penciptaan Manusia Pada Qur’an Karim dan Terjemah Artinya Cetakan UII Yogyakarta - Sudawam, M. Rozik; Hoirus Sholeh, Muhammad (Universitas Islam Negeri Imam Bonjol Padang, 2022)
Qur'an Karim dan Terjemah Artinya published by Universitas Islam Indonesia (UII) Yogyakarta is one of the al-Qur'an translations in Indonesia. The work has characteristics that distinguish it from other translations. The translation tried to bring the meaning of Quranic verses ignoring literal meaning and looking for its equivalent in Bahasa Indonesia. This research is focusing on the verses of the creation of man with a question about the form and style of the translation of these verses. This study uses the theoretical framework of ḥarfiyyah and tafsīriyyah translation, as well as the theory of interpretation patterns in 'Ulūm al-Qur'ān. This study found that the translator uses two translation methods, the ḥarfīyyah, and tafsīriyyah translation methods. Sometimes a verse was translated with a shorter or longer Bahasa Indonesia sentence to clarify the meaning of the verse. The translation of the Qur'an is also considered as an interpretation in a limited version so that the translator has a style in translating the verse. The translation style used is the adabī-ijtimā'ī style with a language approach because the translator uses straightforward language in translating the verse.